Pengaruh Kualitas Pelayanan Terhadap Kepuasan Nasabah dan Dampaknya pada Loyalitas Nasabah PT. BPD Sultra Cabang Bau-Bau - Kurnia Waty; La Hatani; Nursaban Rommy (Jurnal Mahasiswa Manajemen dan Akuntansi, 2026)
This study arises from the urgency to emphasize service quality as a determining factor in fostering both customer satisfaction and loyalty within the competitive banking sector. The research objectives include mapping and evaluating the influence of service quality on customer satisfaction, its impact on loyalty, and the role of satisfaction as a mediating variable at Bank Sultra Bau-Bau Branch. A quantitative approach was applied through a cross-sectional survey, with questionnaires distributed to respondents consisting of 95 selected customers determined using Slovin's formula from the branch's total population. The data were analyzed using Partial Least Squares (PLS) version 4.0 to examine the interactions among variables both directly and through mediation. The findings reveal that service quality exerts a positive and significant effect on customer satisfaction and loyalty, while customer satisfaction also significantly influences loyalty. Furthermore, satisfaction functions as a partial mediator in the relationship between service quality and loyalty, highlighting the necessity of continuously improving service quality to strengthen customer satisfaction and loyalty.